2011
DOI: 10.1109/tgrs.2011.2142419
|View full text |Cite
|
Sign up to set email alerts
|

Component Analysis-Based Unsupervised Linear Spectral Mixture Analysis for Hyperspectral Imagery

Abstract: Two of the most challenging issues in the unsupervised linear spectral mixture analysis (ULSMA) are: 1) determining the number of signatures to form a linear mixing model; and 2) finding the signatures used to unmix data. These two issues do not occur in supervised LSMA since the target signatures are assumed to be known a priori. With recent advances in hyperspectral sensor technology, many unknown and subtle signal sources can now be uncovered and revealed and such signal sources generally cannot be identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…4, the unmixed results were similar to those obtained in [31] and [32] where all abundance fractions were focused on a single mineral signature because none of the pixels in TE was pure and they all violated ASC. Since the results are very similar and many details can be found in [31] and [32], the experiments are not included.…”
Section: Synthetic Image Experimentssupporting
confidence: 73%
See 1 more Smart Citation
“…4, the unmixed results were similar to those obtained in [31] and [32] where all abundance fractions were focused on a single mineral signature because none of the pixels in TE was pure and they all violated ASC. Since the results are very similar and many details can be found in [31] and [32], the experiments are not included.…”
Section: Synthetic Image Experimentssupporting
confidence: 73%
“…Most recently, it has been shown in [27] and [28] that LSU could be effective even only a small number of bands are used. According to a recently developed concept, virtual dimensionality (VD) in [1], [10], and [29], if a signature used to unmix data by LSU can be effectively represented by a spectral band, VD can be further used to determine the number of signatures needed for LSU to perform effectively [30]- [32]. The issue remained is how to find appropriate signatures that correspond to these spectral bands.…”
Section: Introductionmentioning
confidence: 99%
“…As for the CE data, the number of signatures for FCLS to generate was set to 18 as suggested by Chang et al (2010Chang et al ( , 2011a, and Figs. 9.25 and 9.26 show 18 signatures found for HYDICE data by RSQ FCLS-EFA and RSC FCLS-EFA where three realizations were generated respectively.…”
Section: Discussion On Rfcls-efamentioning
confidence: 99%
“…While the results have shown some success they also demonstrated that VD must adapt its value to various applications. For example, the number of endmember should not be the same as the number of signatures used for linear unmixing [3,[6][7]. Also, the number of dimensions required by DR is not the same as the number of bands required to be selected by BS [3,[8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to address this issue an unsupervised algorithm must be included to be able to remove the same type of anomalies to avoid being counted multiple values of VD. This new concept has not been found in any work in [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], specifically, [18].…”
Section: Introductionmentioning
confidence: 99%